Comparison of Calcium Balancing Strategies During Hypothermic Acclimation of Tilapia (Oreochromis mossambicus) and Goldfish (Carassius auratus) - Han, Tsung-Yu; Wu, Chien-Yu; Tsai, Han-Chuan; Cheng, Yi-Pei; Chen, Wei-Fan; Lin, Tzu-Chien; Wang, Chia-Yih; Lee, Jay-Ron; Hwang, Pung-Pung; Lu, Fu-I (Frontiers in Physiology, 2018)
The body temperatures of teleost species fluctuate following changes in the aquatic environment. As such, decreased water temperature lowers the rates of biochemical reactions and affects many physiological processes, including active transport-dependent ion absorption. Previous studies have focused on the impacts of low temperature on the plasma ion concentrations or membrane transporters in fishes. However, very few in vivo or organism-level studies have been performed to more thoroughly elucidate the process of acclimation to low temperatures. In the present study, we compared the strategies for cold acclimation between stenothermic tilapia and eurythermic goldfish. Whole-body calcium content was more prominently diminished in tilapia than in goldfish after long-term cold exposure. This difference can be attributed to alterations in the transportation parameters for Ca2+ influx, i.e., maximum velocity (Vmax) and binding affinity (1/Km). There was also a significant difference in the regulation of Ca2+ efflux between the two fishes. Transcript levels for Ca2+ related transporters, including the Na+/Ca2+ exchanger and epithelial Ca2+ channel, were similarly regulated in both fishes. However, upregulation of plasma membrane Ca2+ATPase expression was more pronounced in goldfish than in tilapia. In addition, enhanced Na+/K+-ATPase abundance, which provides the major driving force for ion absorption, was only detected in tilapia, while upregulated Na+/K+-ATPase activity was only detected in goldfish. Based on the results of the present study, we have found that goldfish and tilapia differentially regulate gill epithelial plasma membrane Ca2+-ATPase (PMCA) expression and Na+/K+-ATPase activity in response to cold environments. These regulatory differences are potentially linked to more effective regulation of Ca2+ influx kinetics and better maintenance of whole body calcium content in goldfish than in tilapia.